Interactions in Swiss Households' Energy Demand: A Holistic Approach - Ivan Tilov; Benjamin Volland; Mehdi Farsi (University of Neuchâtel, Institute of Economic Research (IRENE), 2017)
This article explores the interactions between direct and embodied energy requirements of households in Switzerland in order to assess the net impacts of standard energy policies focusing exclusively on direct energy use. For this purpose, we estimate direct and embodied energy demand of Swiss households by combining consumption data of a national expenditure survey with corresponding data on energy intensity mainly from life-cycle analysis. We find strong evidence of complementarity between direct and grey energy by first estimating model parameters in a system of equations setup. In particular, the analysis of various socio-economic and psychological determinants allows us to identify a non-linear relationship between energy demand and income, which suggests that energy possesses certain "luxury features" that go beyond staple resources. An additional indication that households in Switzerland use direct and indirect energy in a complementary manner is provided by the coefficient of cross-equation correlation of residuals in our system. Finally, we analyze the causal relationship between both energy domains by the method of instrumental variables and find indicative evidence of a positive causal effect of embodied on direct energy demand, but not the other way round. From a policy perspective, our findings are important as they suggest that the wide-spread policies targeting direct energy consumption are unlikely to cause a substantial shift in household energy demand from the direct to the indirect domain.
Keywords: Q40; Q41; D12; 330; Households Energy Requirements; Direct Energy; Embodied Energy; Interactions; Trade-offs; Complementarity